2017
DOI: 10.1186/s40425-017-0267-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictive role of PD-L1 expression in the response of renal Medullary carcinoma to PD-1 inhibition

Abstract: BackgroundRenal medullary carcinoma is one of the rarest malignancies arising from the kidney. Despite various aggressive therapeutic regimens, mortality remains significantly high (95%) with a median overall survival of 5 months. Furthermore, the scarcity of this malignancy renders randomized clinical trials impossible. We examined the expression of programmed death ligand 1 (PD-L1) in two new renal medullary carcinoma cases, investigated their responses to the PD-L1 inhibitor nivolumab and explored the predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 19 publications
1
23
0
3
Order By: Relevance
“…Another young adult patient with recurrent INI1-negative renal medullary carcinoma had a complete response to nivolumab lasting greater than nine months despite low TMB (41). Two subsequent adult patients with INI1-negative renal medullary carcinoma treated with nivolumab did not have durable responses (42). A single-arm phase II trial of nivolumab plus ipilimumab in adults with INI1-negative renal medullary carcinoma in adults is now open [NCT03274258] (43).…”
Section: Patients Treated With Immune Checkpoint Inhibitionmentioning
confidence: 99%
“…Another young adult patient with recurrent INI1-negative renal medullary carcinoma had a complete response to nivolumab lasting greater than nine months despite low TMB (41). Two subsequent adult patients with INI1-negative renal medullary carcinoma treated with nivolumab did not have durable responses (42). A single-arm phase II trial of nivolumab plus ipilimumab in adults with INI1-negative renal medullary carcinoma in adults is now open [NCT03274258] (43).…”
Section: Patients Treated With Immune Checkpoint Inhibitionmentioning
confidence: 99%
“…Although robust data support the use of immunotherapies in many solid tumors, including UC, the efficacy of these agents in renal medullary carcinoma (RMC) is not well established. Published case reports provide a hint of activity in this rare disease . Given the lack of standard treatment options with proven efficacy, an ICI in the setting of a clinical trial is a reasonable approach in this under‐researched population.…”
Section: Introductionmentioning
confidence: 99%
“…Published case reports provide a hint of activity in this rare disease. 14,15 Given the lack of standard treatment options with proven efficacy, an ICI in the setting of a clinical trial is a reasonable approach in this under-researched population.…”
Section: Introductionmentioning
confidence: 99%
“…PD-L1 was expressed in 23% of tumor cells in this patient. Sodji et al 27 later note that PD-L1 levels may not correlate with the amount of response to nivolumab. In their study of 2 patients with RMC, response to nivolumab was observed only in the patient whose tumor had the lowest rate of PD-L1 expression, present in 25% of tumor cells.…”
Section: Current Treatment and Prognosismentioning
confidence: 99%